PERLINDUNGAN HUKUM PEMEGANG HAK ATAS TANAH PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP ( PTSL ) DALAM PERSPEKTIF KEPASTIAN HUKUM - Rajasa, Aqsha; Rini, Indrati (Fakultas Hukum Universitas Narotama, 2025)
The Complete Systematic Land Registration (PTSL) program is a national initiative aimed at accelerating land registration in Indonesia to ensure legal certainty and protection for landowners. However, the implementation of PTSL has raised legal issues, particularly concerning the protection of land rights holders in cases of overlapping claims, administrative errors, and disputes arising after certification. This study aims to analyze the extent of legal protection provided to landowners within the PTSL framework and evaluate the program from the perspective of legal certainty. Using a normative juridical method supported by empirical data, this research examines relevant regulations, legal principles, and case studies from several regions. The findings indicate that while PTSL contributes significantly to land certification, the effectiveness of legal protection is limited by inconsistencies in local land data, lack of public legal awareness, and insufficient dispute resolution mechanisms. To strengthen legal certainty, the study recommends the improvement of land data integration, enhanced legal education for the public, and the establishment of more accessible and responsive legal remedies for aggrieved land rights holders. Keywords: PTSL, protection, landowner